Restorative justice as customized creativity: Tinker Bell’s magic - Talbert, Bonnie (Frontiers in Sociology, 2024)
While many scholars have noted a rise in boredom coinciding with the emergence of modern capitalism, philosophers have long maintained that boredom is part of the horizon of human experience. Although specific social conditions may exacerbate it, boredom will never be completely eradicated, though it signals that something is amiss and requires repair. Recently, cultural criminology has highlighted that boredom and monotony can trigger criminal behavior. If boredom is a contributing factor to crime, then I propose that creative, restorative justice practices can be seen as an antidote to making things right through obligations that restore the dignity and meaning of a victim's life.